INTEGRATION OF EDUCATION WITH CULTURE IN COMPREHENSIVE SCHOOLS - Nigora Akbarovna Sharopova (Web of Journals Publishing, 2024)
This article provides information on ways to teach students to think creatively and how to use them in the development of the cultural-educational environment, heuristic methods of teaching students independent creative thinking and research. Also, various creative activities were recommended to develop creative thinking and creative research among students.
Keywords: general education schools, cultural environment, students, creative thinking, creative activity, heuristic methods, cognitive methods.